From a descriptive label to a guiding principle: the conceptual roots of national security in the People’s Republic of China - Vuori, Juha A.; Gong, Jeremy (Springer Science and Business Media LLC, 2026)
Why did it take so long for the People’s Republic of China (PRC) to adopt the concept of national security (国家安全, guójiā ānquán) into its political lexicon? The present article is the first to fully uncover the conceptual roots of national security in the PRC in order to show the conditions of possibility necessary for the concept to gain performative political power in its political discourse. Looking at the conceptual history of security shows how Chinese political leaders for a long time wielded threat politics without using the term security. While there are studies that have pointed out the introduction of the concept in post-Mao China, and studies that focus on the contemporary applications of the term, the article contributes to this literature by providing a fully-fledged conceptual history of security in mainland China that goes beyond the era of the PRC and connects the conceptual development with political conditions of possibility. By doing so, the article explains why the PRC used other concepts than security in its threat politics compared to other major powers to wield similar performative power. Uncovering the conceptual roots of internationally relevant notions and practices in non-democratic political orders is vital to understand how security operates beyond liberal democracies that most critical studies of security focus on. This highlights the tension between revolution and security in the context of the PRC.